PLACE OF THE PROSECUTOR’S OFFICE IN THE MODERN SYSTEM OF PUBLIC AUTHORITIES AND LAW ENFORCEMENT BODIES - Банах, Сергій Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to determine the place of the prosecutor’s office in the current system of public authorities and law enforcement bodies. Methods: analysis, synthesis, induction, deduction, abstraction, concretization, generalization. Results: author’s conclusions about the place of the prosecutor’s office in the modern system of public authorities and law enforcement bodies. Discussion: the general theoretical approaches to understanding the place of the prosecutor’s office in the modern system of public authorities and law enforcement bodies of Ukraine have been clarified. The author notes that according to the new legislation on the prosecutor’s office and the adoption of amendments to the Constitution of Ukraine in 2016, a gradual implementation of the model of the prosecutor’s office, which presupposes its belonging to the judicial system with some autonomy, is noticeable. It is established that the prosecuting authorities are involved in the exercise of the main function of the judiciary - the administration of justice, but as a representative of the prosecution, that is, there is no neutral position, which is the main feature of the subject of the judiciary. In carrying out the charges in court, the prosecutor actually represents the state in the indictment perspective, fulfills the powers vested in him by law, which is more characteristic of the subject of the executive branch of power. The author argues that an important indication that the prosecutor’s office cannot be part of the judicial branch is its structure and organization with clear vertical subordination and authority. The place of the prosecutor’s office in the system of public authorities is determined by the functions and tasks entrusted to this law enforcement agency and the importance for the state as a guarantor of legality. The lack of a constitutional function of prosecutorial oversight of law enforcement requires state bodies, non-governmental organizations, citizens to understand the new model of its functioning and gradually transfer responsibility to the competent bodies established in the state to ensure law and order. The author emphasizes that a number of reforms of the judicial and law enforcement systems have influenced and changed the role and place of the prosecuting authorities in the system of public authorities. However, the current legislation does not explicitly indicate that the prosecutor’s office belongs to a specific branch of power. Recommendations on determining the place of the prosecutor’s office in the current system of public authorities and law enforcement agencies of Ukraine have been provided.